The Adsorption Ability of Cibacron Red Dye from Aqueous Solution Using Copper Oxide Nanoparticles (Baghdad Science Journal, 2024)
This research describes the environmentally friendly production of CuO nanoparticles utilizing watercress plant extract and calcination at 400 C for 3 hours. SEM and TEM were used to analyze the size of nanoparticles. X-ray diffraction (XRD) was used to determine their crystal structure. Energy-dispersive X-ray spectroscopy (EDX) analysis of the created product's structure revealed just copper and oxygen constituents, demonstrating the purity of the synthetic material. The addition of CuO NPs improved the absorption of the dye Cibacron red. At 35 minutes of contact time, quicker adsorption of Cibacron red dye onto CuO nanoparticles was observed. The Freundlich isotherm and kinetic of pseudo-second order with R2 values more than 0.9785 and 0.999, respectively, were the most effective in describing the adsorption process. The thermodynamic parameters were calculated using thermodynamic analysis. It can be concluded that CuO NPs are an effective adsorbate surface for the Cibacron red dye.